The impact of digital technologies on increasing learning efficiency in the STEM/STEAM context - Ileana Simona SEREMET (Acta et Commentationes, Sciences of Education, 2025)
In the era of information, the techno-scientific revolution, and digital systems, it becomes essential to know how to cope with the information explosion, how to structure information, and especially how to create new knowledge. The integration of digital technologies into school subjects increases the demands placed on human intellect, steering the learning process toward the development of new action-centered methods and techniques. This study addresses certain challenges in the use of digital equipment and presents perspectives for the effective application of digital technologies in STEM/STEAM lessons and activities. The impact of digital technologies is reflected in the increased efficiency of learning and the development of students' algorithmic thinking. Additionally, the study explored students' views regarding the need to implement digital technologies in classroom activities. The findings revealed that when adequately integrated into educational approaches, digital technologies can be considered an important tool that stimulates reflective and conscious learning.